The impact of contextual factors on the implementation of the e-education policy in previously disadvantaged areas in Cape Town: the teachers perspective - Sehuhula-Mooketsi, Bojelo Ester (Department of Information Systems, 2017)
Despite the fact that it has been established that contextual factors affect implementation and implementation outcomes of ICT projects, there is a dearth of information on the impact of contextual factors on the implementation of the white paper in e-education in schools in previously disadvantaged areas in South Africa. To fill this gap, this study investigated how contextual factors affected the implementation and implementation outcomes of the white paper in e-education in schools in previously disadvantaged areas. In addition, the study sought to evaluate if these interventions added value to the teachers work. This study adopted a critical interpretivist approach and used the contextual interaction theory to guide the investigation. The research data was obtained through semi structured interviews with teachers and school management staff of public schools in previously disadvantaged areas in Cape Town, a panel discussion and review of the pertinent policy documents on Information Communication and Technology implementation in South African government schools. The findings of the study show that the implementation context, the history of the implementers, interactions between the policy actors and other issues that are in no way related to the implementation process affected the implementation process and outcomes. Furthermore, the implementation process was wrought with high degrees of ambiguity which is typical in public sector ICT policy implementation. The study also shows that there is need to have measures to evaluate ICT policy implementation which take into consideration the context in which the project exists and the perception of the intended recipients about the success or failure of the implementation. It is hoped that the results will assist those who carry out ICT implementation projects in disadvantaged areas in South Africa and similar context elsewhere insights into the implementation dynamics which can affect implementation outcomes. This thesis contributes to the knowledge base for effective implementation of e-policies, particularly in contexts such as previously disadvantaged areas by pointing out contextual issues and factors that mitigate against implementation efforts. The thesis also reveals practical implications for policy makers by highlighting the need for policies to be based on valid assumptions and be suitable to implementation contexts reflecting the needs, understandings and social realities of primary beneficiaries.